THE EFFECT OF UMP, INVESTMENT AND TPAK ON GROWTH ECONOMY IN JAVA MIDDLE - Sufriyandi; Sebayang, Karuniana Dianta; Suparno (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
This study aims to determine the effect of provincial minimum wages, investment and labor force participation rate on economic growth in Central Java. The research method used in this study is in the form of panels data from 2016 to 2020 in Regencies/Cities in Central Java Province with a descriptive quantitative model. Data is presented annually obtained from BPS Central Java Province. based on the results of the partial analysis, the variables of the provincial minimum wages, investment and labor force participation rate has a positive and significant effect on economic growth in Central Java, which is seen from the probability value which is smaller than (0.05). Simultaneously all research variables have a significant effect on economic growth and have an influence shown by R 2 of 50.20%, indicating that all research variables can explain variables Y and the remaining 49.80% is explained by other variables outside the study.